The development of the k0 method in Peru: Past, present, and future perspectives - Montoya, Eduardo (2010)
The k0 method was implemented at the Peruvian Institute of Nuclear Energy (IPEN), by 1993. Since the middle of 1994, almost all INAA work at IPEN is performed by the k0 method. The establishment, applications, development and future of the method in Peru are presented from a retrospective and prospective view. Attention is paid to difficult aspects, e. g. counting efficiency, characterization of irradiation facility; non ideal behaviour of the epithermal neutron spectrum and consistency of nuclear input data.